BUDAYA HEALING SEBAGAI GAYA HIDUP DI KALANGAN GEN-Z - Nida Musyarofah; Stevany Afrizal (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
This study aims to understand healing culture as a lifestyle among Gen Z, particularly students at Sultan Ageng Tirtayasa University. Using a qualitative approach through in-depth interviews with seven informants, this study analyzes the meaning of healing, its driving factors, and its impact on the daily lives of Gen Z. The results show that healing is interpreted as an effort to calm oneself from academic and social pressures through simple activities such as resting, watching, and traveling. Social media also shapes how Gen Z practices healing, shifting it into a lifestyle trend. The culture of healing has a positive impact in the form of increased psychological comfort and reduced stress, but it also has negative effects such as consumptive behavior, procrastination, and the tendency to use healing as an escape. This study confirms that healing not only functions as mental recovery, but also as an expression of the identity of the younger generation in the digital age. Furthermore, the findings indicate that the practice of healing among Gen Z cannot be separated from the influence of digital culture and social interaction in online spaces. The representation of healing activities on social media platforms also contributes to shaping new social norms and expectations regarding how young people manage stress and express their well-being. Therefore, understanding healing culture is important to see how lifestyle, media influence, and psychological needs intersect in shaping the daily experiences of Gen Z.